Effects of soybean meal particle size on growth performance of nursery pigs - Lawrence, K.R.; Hastad, C.W.; Webster, M.J.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 360 pigs were used in two experiments to determine the effects of decreasing particle size of soybean meal on nursery pig performance. In Exp. 1, pigs were fed diets containing 34% extrudedexpelled soybean meal ground to 965, 742, or 639 microns. In Exp. 2, pigs were fed the same diet containing solvent extracted soybean meal ground to 1226, 797, or 444 microns. Decreasing soybean meal particle size did not influence pig growth performance in either study.
Keywords: Swine; Pigs; Soybean meal; Particle size